Exploring Key Factors Shaping the Effectiveness of Mobile Banking in Pokhara’s Financial Landscape - Karmacharya, Bibek (Journal of Interdisciplinary Studies, 2023)
In the contemporary financial landscape with the anticipated transformation of engagements through mobile banking, this study aims to understand the factors influencing the efficacy of mobile banking services in the Pokhara valley. Using a survey approach with 410 participants, the Confirmatory Factor Analysis indicates a well-fitting measurement model (RMSEA=0.034, GFI=0.941, AGFI=0.923, χ2/df = 1.486, CFI=0.901, TLI=0.887). Key associations reveal that User Adoption negatively impacts effectiveness, while Security Concerns, Ease of Use, and Customer Support positively influence it. Technical Issues, however, have a negative effect. The Squared Multiple Correlation for Mobile Banking Effectiveness is 0.608, emphasizing a substantial proportion of explained variance. Implications stress the need for Pokhara valley financial institutions to recognize and address user adoption and security concerns, with strategic efforts focusing on user education and technological support to enhance mobile banking effectiveness.